Investigation on Neutron Flux Effect onto Irradiated Fuel Burn-up Stored in the Reactor TRIGA PUSPATI - M.A.A. Husain; S. Hashim; D. Bradley; M.H. Rabir; N. Zakaria; M.R.M. Zin (Atom Indonesia, 2019)
An investigation on the out-core neutron flux in the Reactor TRIGA PUSPATI is carried out in this work to determine whether the thermal and/or fast neutron from the core would cause burn-up of the irradiated fuel stored in the same vicinity of the reactor core. The storage rack is positioned at 1 m from the central thimble.MCNPX code is used to calculate the fast and thermal neutron flux at 750 kW reactor power using 10 cm x 10 cm x 10 cm mesh while MATLAB model on 20 cm x 20 cm mesh model is used to plot the axial and radial distribution of the neutron flux density. The results show that the thermal neutrons occurred at  energy lower than 1 x 10-6 MeV and traveled to a maximum distance of 78 cm. The greatest flux for thermal and fast neutrons is 1 x 1013 n.cm2.s-1 and 5 x 1013 n.cm2.s-1 respectively.  The fission-rate of the fuel in the core is determined to be 3.18 x 1014 particle/s compared to 1.51 x 107 particle/s of the irradiated fuel in the storage rack. The burn-up of the fuel in the storage rack is in the order of micrograms and therefore is negligible. It is concluded that neutron flux from the core would not impart burn up effect onto the irradiated fuel stored at the storage rack in the reactor pool.